Termal/mineral springs industry: Need for transformation in function of tourism - Ace Milenkovski; Mijalce Gjorgievski; Dejan Nakovski (UTMS Journal of Economics, 2018)
Wellness tourism has now grown into a serious form of tourist movement and is an important part of the tourism industry with significant economic impact. Within the framework of wellness tourism it covers more sectors, among which are: Spa, Wellness Tourism, Thermal/Mineral Springs, Workplace Wellness, and Wellness Lifestyle Real Estate. The wellness economy now represents more than 5% of global economic output and is almost half the size of all global health expenditures, which reached 7.6 trillion in 2014. In 2015, there were 121,595 spas operating around the world, earning 77.6 billion in revenues, leader in total spa revenues is Europe, the number of spas has continued to increase and their revenue growth has been strong in local currency. The aim of the authors in the paper is to present the situation with the Thermal/Mineral Springs Industry in the Republic of Macedonia. Due to these statistical data, the authors are on the opinion that it is necessary to transform the Thermal/Mineral Springs Industry in the function of health tourism, which is also the subject of the research in this paper.
Keywords: L83; Z32; I15; O18; 330; wellness; development; policy; tourist demand